DEVELOPING A COMPETITIVE REWARD SYSTEM TO ATTRACT QUALIFIED TEACHERS - Rotty, Viktory N.J.; Sumual, Tinneke; Lumapouw, Harol (International Journal of Social Service and Research, 2024)
The quality of education plays an important role in determining educational outcomes, as competent and dedicated educators are able to provide effective teaching, motivate students, and help them reach their full potential. However, in many countries, including Indonesia, there are still challenges in attracting and retaining quality educators. Therefore, it is important for educational institutions to formulate a reward system that is not only financially competitive, but also includes non-financial aspects that can improve the satisfaction and motivation of educators. This study employs a descriptive qualitative approach. Data collection was conducted through a literature review, focusing on relevant written sources such as books, journal articles, research reports, theses, and dissertations. Data analysis was conducted using triangulation to compare and confirm information from various sources, providing a more comprehensive and reliable understanding of the topic being studied. The results show that the development of a competitive reward system is critical to attracting quality educators, who are key to improving the quality of educational education. Education institutions can create an atmosphere that supports the improvement of teaching quality and education as a whole by implementing a balanced reward system and considering feedback from educators.